Understanding Gender Equality Policy and Practice Gaps Through the Lens of Organisational Justice: Development of an Employee Alignment Model - McCarthy, Chrissi; Barnard, Sarah; Thomson, Derek; Dainty, Andrew (Frontiers in Sociology, 2021)
Policies and actions to address gender inequalities are widespread across a range of institutional and organisational contexts. Concerns have been raised about the efficacy and impacts of such measures in the absence of sustained evaluation of these activities. It has been proposed that important contextual factors may propel or inhibit measures to promote gender equality, including a critical mass of women, role models, diverse leaders and inclusive organisational cultures. This paper explores relationships between organisational justice and equality interventions to better understand gaps between equality policies and practices using a comparative case study approach in a male-dominated sector. A combination of questionnaire and interview data analysis with employees in three case organisations in the construction sector are used to outline links between perceptions of gender equality initiatives and organisational justice, and the mechanisms used to reinforce in-group dominance. The findings culminate in the development of an Employee Alignment Model and a discussion of how this relates to the organisational climate for gender equality work. The findings suggest that the development of interactional organisational justice is an important precursor for successful gender equality interventions in organisations. These findings have implications for those looking to minimize unintentional harm of policies or interventions to improve gender equality.